Improvement of the uric acid determination by the carbonate method for serum and urine. Issue 4 (July 1961) - Eichhorn, F.; Zelmanowski, S.; Lew, E.; Rutenberg, A.; Fanias, B.
Abstract : An improved colorimetric procedure for determining uric acid by the carbonate method in serum and urine is described, using a 20% sodium carbonate solution with urea. Reliable results are also obtained in high concentrations of uric acid.